2020
DOI: 10.1093/jhps/hnab024
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed models for periacetabular osteotomy surgical planning

Abstract: The purpose of this study was to determine the feasibility and clinical benefits of using 3D-printed hemipelvis models for periacetabular osteotomy preoperative planning in the treatment of hip dysplasia. This retrospective study included 28 consecutive cases in 26 patients, with two bilateral cases, who underwent periacetabular osteotomy between January 2017 and February 2020 and had routine radiographs, CT and MR imaging. Of these, 14 cases [mean patient age 30.7 (SD 8.4) years, 11 female] had routine preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…20 Markhardt et al observed that the reduction of operation time, including the average time to reach the appropriate acetabular position and the average total PAO time, improved operation efficiency. 21 In this study, the same results were found. Meanwhile, the use of PSI has greatly simplified the positioning of special osteotomy angles and positions during acetabular osteotomy.…”
Section: Discussionsupporting
confidence: 85%
“…20 Markhardt et al observed that the reduction of operation time, including the average time to reach the appropriate acetabular position and the average total PAO time, improved operation efficiency. 21 In this study, the same results were found. Meanwhile, the use of PSI has greatly simplified the positioning of special osteotomy angles and positions during acetabular osteotomy.…”
Section: Discussionsupporting
confidence: 85%
“…A glimpse at the future would reflect major advances related to individual planning, surgical training, and precise surgical conduction. This will include 3D modeling and printing as well as individualized cutting guides that aid the planning and conduction of the procedure [ 43 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…These approaches allow one to measure radiographic parameters in real-time before and after virtual surgical interventions, including osteotomies and osteoplasties. The introduction of 3D printing of CT-derived anatomy allows for hands-on understanding of the bony morphology which also aids in surgical decision-making ( 53 ). While the details of these advanced techniques are beyond the scope of this article, their prospect is certainly noteworthy.…”
Section: Ct For Preoperative Planningmentioning
confidence: 99%